Postpartum Depression: Current Status and Possible Identification Using Biomarkers - Yu, Yi; Liang, Hong-Feng; Chen, Jing; Li, Zhi-Bin; Han, Yu-Shuai; Chen, Jia-Xi; Li, Ji-Cheng (Frontiers in Psychiatry, 2021)
Postpartum depression (PPD) is a serious health issue that can affect about 15% of the female population within after giving birth. It often conveys significant negative consequences to the offsprings. The symptoms and risk factors are somewhat similar to those found in non-postpartum depression. The main difference resides in the fact that PPD is triggered by postpartum specific factors, including especially biological changes in the hormone levels. Patients are usually diagnosed using a questionnaire onsite or in a clinic. Treatment of PPD often involves psychotherapy and antidepressant medications. In recent years, there have been more researches on the identification of biological markers for PPD. In this review, we will focus on the current research status of PPD, with an emphasis on the recent progress made on the identification of PPD biomarkers.